2023
DOI: 10.1117/1.jmi.10.5.051807
|View full text |Cite
|
Sign up to set email alerts
|

Multi-vendor robustness analysis of a commercial artificial intelligence system for breast cancer detection

Abstract: Purpose: Population-based screening programs for the early detection of breast cancer have significantly reduced mortality in women, but they are resource intensive in terms of time, cost, and workload and still have limitations mainly due to the use of 2D imaging techniques, which may cause overlapping of tissues, and interobserver variability. Artificial intelligence (AI) systems may be a valuable tool to assist radiologist when reading and classifying mammograms based on the malignancy of the detected lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Moreover, integrating breast cancer into the IoT framework holds significant potential for early detection and monitoring. Although [10][11][12] have delved into IoT applications in educational settings, none of these works addressed Electronic Health Records (EHRs), nor did they highlight the appropriateness of addressing health-related issues in institutional homes through the implementation of health sensors, as proposed in their research.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…Moreover, integrating breast cancer into the IoT framework holds significant potential for early detection and monitoring. Although [10][11][12] have delved into IoT applications in educational settings, none of these works addressed Electronic Health Records (EHRs), nor did they highlight the appropriateness of addressing health-related issues in institutional homes through the implementation of health sensors, as proposed in their research.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…Cancers 2023, 15, 3069 2 of 12 Studies have reported that AI performance is comparable to or might even outperform humans in the interpretation of screening studies [4][5][6][7][8]. In these studies, performance is often assessed in terms of general outcome metrics such as cancer detection rate and recall rate [9], but information on the prognostic features of screen-detected breast cancers is frequently not provided.…”
Section: Introductionmentioning
confidence: 99%